Adsorbent for removing boron and phosphorus impurities in SiHCl3 as well as preparation method and application of adsorbent
By depositing oxidized metals and amine organic matter on the inorganic porous material support and mixing them to remove boron and phosphorus impurities in trichlorosilicon, the problem of high impurity removal costs in the prior art is solved, and high efficiency and stability are achieved Impurity removal and good renewability.
Patent Information
- Application Number
- CN202411841363.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the method of removing trace amounts of boron and phosphorus impurities in trichlorosilicon has high cost, low product yield and unstable quality.
The inorganic porous material is used as a support to deposit oxidized metals and amine organic matters in sequence, and the products in each step are mixed to remove boron and phosphorus impurities in trichlorosilicon.
It has achieved efficient removal of boron and phosphorus impurities in trichlorosilicon, reduced costs, improved product yield and quality stability, and had good cycle renewability.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polysilicon production, and in particular to an adsorbent for removing boron and phosphorus impurities in trichlorosilane, and a preparation method and application thereof. Background Art
[0002] The modified Siemens process is the mainstream production process of polysilicon, in which the removal of trace boron and phosphorus impurities in the raw material trichlorosilane is very critical, which seriously affects the quality of polysilicon products. At present, the domestic main method of removing trace boron and phosphorus impurities in trichlorosilane is through multi-stage distillation. However, since the volatility of trace boron and phosphorus impurities in trichlorosilane is close to that of trichlorosilane, it is necessary to increase the reflux ratio and reduce the extraction volume during multi-stage distillation to ensure quality indicators, resulting in low product yield and unstable product quality, and the energy consumption and cost for removing boron and phosphorus remain high. Summary of the invention
[0003] The purpose of the present application is to provide an adsorbent for removing boron and phosphorus impurities in trichlorosilane, and a preparation method and application thereof. In the preparation method, an inorganic porous material is used as a carrier, and oxidized metals and amine organic matter are deposited on the carrier in sequence, and the products in each step are mixed to remove boron and phosphorus impurities in trichlorosilane, thereby solving the problem of high cost of removing boron and phosphorus impurities in the prior art.
[0004] In order to achieve one of the above-mentioned purposes of the invention, an embodiment of the present application provides a method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane, comprising the following steps:
[0005] S1: ultrasonically clean the inorganic porous material, and dry the cleaned inorganic porous material to obtain adsorbent A;
[0006] S2: dissolving a metal salt in water to prepare a metal salt solution, mixing the metal salt solution with a portion of the adsorbent A, depositing under vacuum, and then drying;
[0007] S3: heating the adsorbent A on which the metal salt is deposited in step S2 for heat treatment to obtain adsorbent B;
[0008] S4: dissolving an amine organic substance in water to prepare an organic amine solution, and mixing the organic amine solution with a portion of the adsorbent B, depositing under vacuum, and then drying to obtain an adsorbent C;
[0009] S5: mixing adsorbent A, adsorbent B and adsorbent C to obtain a boron and phosphorus impurity adsorbent.
[0010] As a further improvement of an embodiment of the present application, the inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2.
[0011] As a further improvement of one embodiment of the present application, the inorganic porous material has a bulk density of 0.3 to 1.2 g / ml and a specific surface area of 200 to 300 m 2 / g.
[0012] As a further improvement of one embodiment of the present application, the metal salt is selected from one or more of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
[0013] As a further improvement of an embodiment of the present application, the concentration of the metal salt solution is 0.1 to 2 mol / L.
[0014] As a further improvement of one embodiment of the present application, the amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide, and nitrogenmethylformamide.
[0015] As a further improvement of an embodiment of the present application, the concentration of the organic amine solution is 0.1 to 1 mol / L.
[0016] As a further improvement of an embodiment of the present application, in step S3, the heating temperature of the heat treatment is 300-750°C, the heating time is 2-6h, and the heating rate is 2-10°C / min.
[0017] As a further improvement of one embodiment of the present application, the mass ratio of adsorbent A, adsorbent B and adsorbent C is (1-3):(1-2):1.
[0018] One embodiment of the present application also provides an adsorbent for removing boron and phosphorus impurities in trichlorosilane, including an inorganic porous material, an inorganic porous material loaded with oxidized metals, and a mixture of inorganic porous materials loaded with oxidized metals and amine organics, wherein the inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2.
[0019] As a further improvement of one embodiment of the present application, the oxidized metal is formed by heating and oxidizing one or more metal salts of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
[0020] As a further improvement of one embodiment of the present application, the amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide, and nitrogenmethylformamide.
[0021] One embodiment of the present application also provides a use of the adsorbent for removing boron and phosphorus impurities in trichlorosilane as described above, wherein the adsorbent is used to adsorb boron impurities and phosphorus impurities in trichlorosilane.
[0022] One or more technical solutions provided by this application have at least the following technical effects or advantages:
[0023] In the preparation method of the adsorbent for removing boron and phosphorus impurities in trichlorosilane provided in the present application, an inorganic porous material is used as a carrier, and oxidized metals and amine organics are deposited on the carrier in sequence, and the inorganic porous material, the inorganic porous material deposited with oxidized metals, and the inorganic porous material deposited with oxidized metals and amine organics are mixed to remove boron and phosphorus impurities in trichlorosilane. The inorganic porous material provides a stable structure with a high specific surface area and can quickly enrich boron and phosphorus impurities. The oxidized metals and amine organics can complex with phosphorus impurities and boron impurities to enhance the adsorption effect, so that the boron and phosphorus impurities in trichlorosilane are removed at the same time. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below in conjunction with specific embodiments, but these embodiments do not limit the present invention, and changes in reaction conditions, reactants or raw material amounts made by ordinary technicians in the field according to these embodiments are all included in the protection scope of the present invention.
[0025] The present application provides a method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane, comprising the following steps:
[0026] S1: ultrasonically clean the inorganic porous material, and dry the cleaned inorganic porous material to obtain adsorbent A;
[0027] S2: dissolving a metal salt in water to prepare a metal salt solution, mixing the metal salt solution with a portion of the adsorbent A, depositing under vacuum, and then drying;
[0028] S3: heating the adsorbent A on which the metal salt is deposited in step S2 for heat treatment to obtain adsorbent B;
[0029] S4: dissolving an amine organic substance in water to prepare an organic amine solution, and mixing the organic amine solution with a portion of the adsorbent B, depositing under vacuum, and then drying to obtain an adsorbent C;
[0030] S5: mixing adsorbent A, adsorbent B and adsorbent C to obtain a boron and phosphorus impurity adsorbent.
[0031] In the present application, an inorganic porous material is used as a carrier, and the inorganic porous material as a carrier is mixed with a metal salt solution, and after being deposited under vacuum, it is dried to remove moisture, so that the metal salt in the metal salt solution is deposited on the inorganic porous material. After the metal salt deposited on the inorganic porous material is heated for heat treatment, the metal salt is oxidized into an oxidized metal, that is, the metal salt deposited on the inorganic porous material is converted into an oxidized metal. Then the inorganic porous material deposited with the oxidized metal is placed in an organic amine solution, so that the amine compound is also deposited on the inorganic porous material, and finally the cleaned inorganic porous material (adsorbent A), the inorganic porous material deposited with the oxidized metal (adsorbent B) and the inorganic porous material deposited with the oxidized metal and the amine compound (adsorbent C) are mixed to form a boron and phosphorus impurity adsorbent.
[0032] The carriers of adsorbent A, adsorbent B and adsorbent C are all inorganic porous materials, which have strong adsorption due to their large specific surface area. Trichlorosilane has extremely weak polarity, while the phosphorus impurities in trichlorosilane have strong polarity and tend to form addition chemical bonds. The oxidized metal is very easy to react with the phosphorus impurities in trichlorosilane. The oxidized metal is deposited in adsorbent B, which can be used to remove the phosphorus impurities in trichlorosilane. The oxidized metal and amine compounds are deposited in adsorbent C. The lone pair of electrons on N in the amine compound can react with the boron impurities, and the oxidized metal reacts with the phosphorus impurities. After mixing adsorbent A, adsorbent B and adsorbent C, the addition ratio of each adsorbent can be adjusted according to the different concentrations of boron and phosphorus impurities in trichlorosilane, so that the boron impurities and phosphorus impurities in trichlorosilane can be removed at the same time.
[0033] Preferably, the mass ratio of adsorbent A, adsorbent B and adsorbent C is (1-3):(1-2):1.
[0034] In addition, based on the structural stability of the inorganic porous material, the boron and phosphorus impurity adsorbent prepared by the preparation method provided in the present application can be desorbed by heating the complex to decompose, which makes the boron and phosphorus impurity adsorbent highly recyclable and greatly reduces the cost of removing boron and phosphorus impurities with trichlorosilane. And because the inorganic porous material is an inorganic substance with a stable structure, its porous structure will not collapse even if heated.
[0035] In the preparation method provided in the present application, in order to avoid the introduction of new impurities during impurity removal, the inorganic porous material is firstly ultrasonically cleaned before being processed to remove dust and oil stains on the surface of the inorganic porous material.
[0036] Among them, an ultrasonic cleaner is used for ultrasonic cleaning, the cleaning time is 20 to 80 minutes, and the frequency of the ultrasonic cleaner is 10kHz to 90kHz to ensure that the inorganic porous material is cleaned. The cleaning agent is any one of ultrapure water, deionized water, and anhydrous ethanol. The aforementioned solvents are easy to volatilize and not easy to remain, which can avoid the introduction of new impurities caused by incomplete drying. Of course, in addition to ultrapure water, deionized water and anhydrous ethanol, other easy-to-dry solvents can also be used.
[0037] After cleaning, the inorganic porous material is placed in a drying oven and dried at a temperature of 80 to 120° C. for 12 to 48 hours. Since there are many pores in the inorganic porous material, it is necessary to ensure that the cleaning agent in the inorganic porous material is completely dried to obtain a clean inorganic porous material after drying.
[0038] In some embodiments, the inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2. The various inorganic compounds listed above are not flammable and will not cause combustion risks when exposed to fire. When the adsorbent for boron and phosphorus impurities fails to adsorb, heating it can decompose the complex formed by amine organic matter and boron impurities and the complex formed by oxidized metals and phosphorus impurities, so that the adsorbent for boron and phosphorus impurities can be reused. Since the porous material formed by the inorganic substance has a stable structure, its porous structure will not collapse even if it is heated.
[0039] In some embodiments, the inorganic porous material has a bulk density of 0.3 to 1.2 g / ml and a specific surface area of 200 to 300 m 2 / g. The macroscopic morphology of inorganic porous materials is spherical or cylindrical. Using inorganic porous materials with a smaller packing density can better improve their adsorption performance. The larger the specific surface area of inorganic porous materials, the more adsorption sites they have, that is, the stronger their adsorption capacity.
[0040] In some embodiments, the metal salt is selected from one or more of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
[0041] In some embodiments, the concentration of the metal salt solution is 0.1-2 mol / L. For CuCl which is poorly soluble in water, ultrasonic dispersion or other methods can be used to dissolve it in water.
[0042] In some embodiments, the amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide, and nitrogen methylformamide.
[0043] In some embodiments, the concentration of the organic amine solution is 0.1-1 mol / L.
[0044] In some embodiments, in step S3, the heating temperature of the heat treatment is 300-750°C, the heating time is 2-6h, and the heating rate is 2-10°C / min. Heating to 300-750°C is sufficient to oxidize the metal salt to an oxidized state, thereby avoiding increasing the manufacturing cost of the adsorbent. Controlling the heating rate to 2-10°C / min can prevent the oxidized metal supported on the inorganic porous material from sintering into agglomerates.
[0045] In some embodiments, in step S2, the inorganic porous material and the metal salt solution are placed in a vacuum container, evacuated until the pressure displayed on the pressure gauge is -0.2 to 0 MPa, and the deposition time is 30 to 150 min. In step S4, the inorganic porous material and the organic amine solution are placed in a vacuum container, evacuated until the pressure displayed on the pressure gauge is -0.2 to 0 MPa, and the deposition time is 30 to 90 min.
[0046] Since there are many pores in inorganic porous materials, completely immersing the inorganic porous materials in metal salt solutions or organic amine solutions cannot guarantee that the metal salts or amine compounds can well enter the pores of the inorganic porous materials and adhere to the surface. Vacuuming can promote the adhesion rate and adhesion speed of metal salts or amine compounds on inorganic porous materials.
[0047] After the deposition in step S2 is completed, the inorganic porous material with the metal salt deposited thereon is placed in a drying oven for drying to remove water in the metal salt solution so that only the metal salt is attached to the surface of the inorganic porous material, wherein the drying temperature is 80-120° C. and the drying time is 24-48 hours.
[0048] After the deposition in step S4 is completed, the inorganic porous material deposited with amine organic matter is placed in a drying oven for drying to remove water in the organic amine solution so that only amine organic matter is attached to the surface of the inorganic porous material, wherein the drying temperature is 70-110° C. and the drying time is 12-36 hours.
[0049] An embodiment of the present application also provides an adsorbent for removing boron and phosphorus impurities in trichlorosilane, comprising an inorganic porous material, an inorganic porous material loaded with oxidized metals, and a mixture of inorganic porous materials loaded with oxidized metals and amine organics, wherein the inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2.
[0050] The above-mentioned inorganic porous material has a large specific surface area, high structural stability, high melting point and non-flammability. The lone pair of electrons on the N atom in the amine organic matter can be complexed with the boron impurity in trichlorosilane, and the oxidized metal can be complexed with the phosphorus impurity in trichlorosilane, so that the adsorbent has good adsorption effect and efficiency. The decomposition of the complex can be achieved by heating, and heating will not cause the porous structure of the carrier to collapse, so that the adsorbent has good cyclic regenerativeness and there is no risk of combustion.
[0051] In some embodiments, the oxidized metal is formed by heating and oxidizing one or more metal salts of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
[0052] In some embodiments, the amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide, and nitrogen methylformamide.
[0053] The present application also provides an application of an adsorbent for removing boron and phosphorus impurities in trichlorosilane as described above, and the adsorbent is used to adsorb boron impurities and phosphorus impurities in trichlorosilane. Based on the characteristics of the adsorbent for boron and phosphorus impurities described above, the adsorbent for removing boron and phosphorus impurities in trichlorosilane provided in the embodiment of the present application has a high adsorption rate and adsorption speed when adsorbing boron and phosphorus impurities in trichlorosilane, and is regenerable and non-combustible.
[0054] The technical solution of the present application is further described below in conjunction with some specific embodiments.
[0055] Example 1
[0056] S1: The inorganic porous material γ-Al2O3 was added to an ultrasonic cleaner filled with deionized water for ultrasonic cleaning. The working frequency of the ultrasonic cleaner was 30 Hz. After cleaning for 40 minutes, the γ-Al2O3 was placed in a blast drying oven and dried at 100°C for 12 hours to obtain adsorbent A. The bulk density of the inorganic porous material γ-Al2O3 was 0.75 g / ml, and the specific surface area was 280 m 2 / g, the macroscopic morphology is spherical.
[0057] S2: Weigh 13.4 g of CuCl2 to prepare a 1 mol / L CuCl2 solution, mix part of adsorbent A with the CuCl2 solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 60 minutes. Then, put the γ-Al2O3 deposited with CuCl2 into a drying oven and dry it at 100°C for 24 hours.
[0058] S3: The dried γ-Al2O3 on which CuCl2 is deposited is heated for heat treatment to obtain an adsorbent B. The heating temperature of the heat treatment is 500° C., the heating time is 4 h, and the heating rate is 5° C. / min.
[0059] S4: Weigh 19.5 g of N-methyl-D-glucamine to prepare a 1 mol / L N-methyl-D-glucamine solution, mix part of adsorbent B with the N-methyl-D-glucamine solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 30 minutes. Then, put the γ-Al2O3 deposited with N-methyl-D-glucamine and CuCl2 into a drying oven and dry it at 110°C for 12 hours to obtain adsorbent C.
[0060] S5: uniformly mix adsorbent A, adsorbent B and adsorbent C in a mass ratio of 1:1:1 to obtain a boron and phosphorus impurity adsorbent.
[0061] The above-synthesized mixed adsorbent was used to remove boron and phosphorus impurities in SiHCl3. The experimental method was as follows:
[0062] Before adsorption, the mixed adsorbent was dried at 150 °C for 4 h.
[0063] Weigh 5g of mixed adsorbent and add it to 100ml SiHCl3 solution. Seal the solution containing adsorbent in a 100mL square-mouth bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the mixed adsorbent for boron impurities is 98%, and the removal rate of phosphorus impurities is 99%.
[0064] Example 2
[0065] S1: The inorganic porous material γ-Al2O3 was added to an ultrasonic cleaner filled with deionized water for ultrasonic cleaning. The working frequency of the ultrasonic cleaner was 30 Hz. After cleaning for 40 minutes, the γ-Al2O3 was placed in a blast drying oven and dried at 100°C for 12 hours to obtain adsorbent A. The bulk density of the inorganic porous material γ-Al2O3 was 0.75 g / ml, and the specific surface area was 280 m 2 / g, the macroscopic morphology is spherical.
[0066] S2: Weigh 6.7 g of CuCl2 to prepare a 0.5 mol / L CuCl2 solution, mix part of adsorbent A with the CuCl2 solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 60 minutes. Then, put the γ-Al2O3 deposited with CuCl2 into a drying oven and dry it at 100°C for 24 hours.
[0067] S3: The dried γ-Al2O3 on which CuCl2 is deposited is heated for heat treatment to obtain an adsorbent B. The heating temperature of the heat treatment is 500° C., the heating time is 4 h, and the heating rate is 5° C. / min.
[0068] S4: Weigh 19.5 g of N-methyl-D-glucamine to prepare a 1 mol / L N-methyl-D-glucamine solution, mix part of adsorbent B with the N-methyl-D-glucamine solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 30 minutes. Then, put the γ-Al2O3 deposited with N-methyl-D-glucamine and CuCl2 into a drying oven and dry it at 110°C for 12 hours to obtain adsorbent C.
[0069] S5: uniformly mix adsorbent A, adsorbent B and adsorbent C in a mass ratio of 1:1:1 to obtain a boron and phosphorus impurity adsorbent.
[0070] The above-synthesized mixed adsorbent was used to remove boron and phosphorus impurities in SiHCl3. The experimental method was as follows:
[0071] Before adsorption, the mixed adsorbent was dried at 150 °C for 4 h.
[0072] Weigh 5g of mixed adsorbent and add it to 100ml SiHCl3 solution. Seal the solution containing adsorbent in a 100mL square-mouth bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of boron impurities by the mixed adsorbent is 98%, and the removal rate of phosphorus impurities is 85%.
[0073] Example 3
[0074] S1: The inorganic porous material γ-Al2O3 was added to an ultrasonic cleaner filled with deionized water for ultrasonic cleaning. The working frequency of the ultrasonic cleaner was 30 Hz. After cleaning for 40 minutes, the γ-Al2O3 was placed in a blast drying oven and dried at 100°C for 12 hours to obtain adsorbent A. The bulk density of the inorganic porous material γ-Al2O3 was 0.75 g / ml, and the specific surface area was 280 m 2 / g, the macroscopic morphology is spherical.
[0075] S2: Weigh 26.8 g of CuCl2 to prepare a 2 mol / L CuCl2 solution, mix part of adsorbent A with the CuCl2 solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 60 minutes. Then, put the γ-Al2O3 deposited with CuCl2 into a drying oven and dry it at 100°C for 24 hours.
[0076] S3: The dried γ-Al2O3 on which CuCl2 is deposited is heated for heat treatment to obtain an adsorbent B. The heating temperature of the heat treatment is 500° C., the heating time is 4 h, and the heating rate is 5° C. / min.
[0077] S4: Weigh 19.5 g of N-methyl-D-glucamine to prepare a 1 mol / L N-methyl-D-glucamine solution, mix part of adsorbent B with the N-methyl-D-glucamine solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 30 minutes. Then, put the γ-Al2O3 deposited with N-methyl-D-glucamine and CuCl2 into a drying oven and dry it at 110°C for 12 hours to obtain adsorbent C.
[0078] S5: uniformly mix adsorbent A, adsorbent B and adsorbent C in a mass ratio of 1:1:1 to obtain a boron and phosphorus impurity adsorbent.
[0079] The above-synthesized mixed adsorbent was used to remove boron and phosphorus impurities in SiHCl3. The experimental method was as follows:
[0080] Before adsorption, the mixed adsorbent was dried at 150 °C for 4 h.
[0081] Weigh 5g of mixed adsorbent and add it to 100ml SiHCl3 solution. Seal the solution containing adsorbent in a 100mL square-mouth bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of boron impurities by the mixed adsorbent is 97%, and the removal rate of phosphorus impurities is 88%.
[0082] Example 4
[0083] S1: The inorganic porous material γ-Al2O3 was added to an ultrasonic cleaner filled with deionized water for ultrasonic cleaning. The working frequency of the ultrasonic cleaner was 30 Hz. After cleaning for 40 minutes, the γ-Al2O3 was placed in a blast drying oven and dried at 100°C for 12 hours to obtain adsorbent A. The bulk density of the inorganic porous material γ-Al2O3 was 0.75 g / ml, and the specific surface area was 280 m 2 / g, the macroscopic morphology is spherical.
[0084] S2: Weigh 20g of (CH3COO)2Cu to prepare a 1mol / L (CH3COO)2Cu solution, mix part of adsorbent A with the (CH3COO)2Cu solution and put it into a vacuum container, evacuate the container to -0.1MPa, and deposit for 60min. Then, put the γ-Al2O3 deposited with (CH3COO)2Cu into a drying oven and dry it at 100°C for 24h.
[0085] S3: The γ-Al2O3 on which (CH3COO)2Cu is deposited after drying is heated for heat treatment to obtain adsorbent B. The heating temperature of the heat treatment is 500°C, the heating time is 4 hours, and the heating rate is 5°C / min.
[0086] S4: Weigh 19.5 g of N-methyl-D-glucamine to prepare a 1 mol / L N-methyl-D-glucamine solution, mix part of adsorbent B with the N-methyl-D-glucamine solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 30 minutes. Then, put the γ-Al2O3 deposited with N-methyl-D-glucamine and (CH3COO)2Cu into a drying oven and dry it at 110°C for 12 hours to obtain adsorbent C.
[0087] S5: uniformly mix adsorbent A, adsorbent B and adsorbent C in a mass ratio of 1:1:1 to obtain a boron and phosphorus impurity adsorbent.
[0088] The above-synthesized mixed adsorbent was used to remove boron and phosphorus impurities in SiHCl3. The experimental method was as follows:
[0089] Before adsorption, the mixed adsorbent was dried at 150 °C for 4 h.
[0090] Weigh 5g of mixed adsorbent and add it to 100ml SiHCl3 solution. Seal the solution containing adsorbent in a 100mL square-mouth bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of boron impurities by the mixed adsorbent is 98%, and the removal rate of phosphorus impurities is 80%.
[0091] Example 5
[0092] S1: Add the inorganic porous material activated carbon into an ultrasonic cleaner filled with deionized water for ultrasonic cleaning. The working frequency of the ultrasonic cleaner is 30 Hz. After cleaning for 40 minutes, put the activated carbon into a blast drying oven and dry it at 100°C for 12 hours to obtain adsorbent A. The bulk density of the inorganic porous material activated carbon is 0.7 g / ml, and the specific surface area is 270 m 2 / g, the macroscopic morphology is spherical.
[0093] S2: Weigh 13.4 g of CuCl2 to prepare a 1 mol / L CuCl2 solution, mix part of adsorbent A with the CuCl2 solution and put them into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 60 minutes. Then, put the activated carbon deposited with CuCl2 into a drying oven and dry it at 100°C for 24 hours.
[0094] S3: The activated carbon on which CuCl2 is deposited after drying is heated for heat treatment to obtain adsorbent B. The heating temperature of the heat treatment is 500° C., the heating time is 4 h, and the heating rate is 5° C. / min.
[0095] S4: Weigh 19.5 g of N-methyl-D-glucamine to prepare a 1 mol / L N-methyl-D-glucamine solution, mix part of adsorbent B with the N-methyl-D-glucamine solution and put it into a vacuum container, evacuate the container to -0.1 MPa, and deposit for 30 minutes. Then, put the γ-Al2O3 deposited with N-methyl-D-glucamine and CuCl2 into a drying oven and dry it at 110°C for 12 hours to obtain adsorbent C.
[0096] S5: uniformly mix adsorbent A, adsorbent B and adsorbent C in a mass ratio of 1:1:1 to obtain a boron and phosphorus impurity adsorbent.
[0097] The above-synthesized mixed adsorbent was used to remove boron and phosphorus impurities in SiHCl3. The experimental method was as follows:
[0098] Before adsorption, the mixed adsorbent was dried at 150 °C for 4 h.
[0099] Weigh 5g of mixed adsorbent and add it to 100ml SiHCl3 solution. Seal the solution containing adsorbent in a 100mL square-mouth bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of boron impurities by the mixed adsorbent is 97%, and the removal rate of phosphorus impurities is 96%.
[0100] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0101] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane, characterized in that: The steps include: S1: ultrasonically clean the inorganic porous material, and dry the cleaned inorganic porous material to obtain adsorbent A; S2: dissolving a metal salt in water to prepare a metal salt solution, mixing the metal salt solution with a portion of the adsorbent A, depositing under vacuum, and then drying; S3: heating the adsorbent A on which the metal salt is deposited in step S2 for heat treatment to obtain adsorbent B; S4: dissolving an amine organic substance in water to prepare an organic amine solution, and mixing the organic amine solution with a portion of the adsorbent B, depositing under vacuum, and then drying to obtain an adsorbent C; S5: mixing adsorbent A, adsorbent B and adsorbent C to obtain a boron and phosphorus impurity adsorbent.
2. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 1, characterized in that: The inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2.
3. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 2, characterized in that: The bulk density of inorganic porous materials is 0.3-1.2 g / ml, and the specific surface area is 200-300 m 2 / g.
4. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 1, characterized in that: The metal salt is selected from one or more of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
5. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 4, characterized in that: The concentration of the metal salt solution is 0.1-2 mol / L.
6. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 1, characterized in that: The amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide and nitrogen methylformamide.
7. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 6, characterized in that: The concentration of the organic amine solution is 0.1 to 1 mol / L.
8. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 1, characterized in that: In step S3, the heating temperature of the heat treatment is 300-750°C, the heating time is 2-6h, and the heating rate is 2-10°C / min.
9. The method for preparing an adsorbent for removing boron and phosphorus impurities in trichlorosilane according to any one of claims 1 to 8, characterized in that: The mass ratio of adsorbent A, adsorbent B and adsorbent C is (1-3):(1-2):
1.
10. An adsorbent for removing boron and phosphorus impurities in trichlorosilane, characterized in that: It includes an inorganic porous material, an inorganic porous material loaded with an oxidized metal, and a mixture of an inorganic porous material loaded with an oxidized metal and an amine organic matter, wherein the inorganic porous material is selected from one or more of activated carbon, InO2, ZrO2, SiO2, γ-Al2O3, CeO2, and TiO2.
11. The adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 10, characterized in that: The oxidized metal is formed by heating and oxidizing one or more metal salts selected from the group consisting of CuCl2, CuCl, (CH3COO)2Mn, (CH3COO)2Cu, and CoCl2.
12. The adsorbent for removing boron and phosphorus impurities in trichlorosilane according to claim 10, characterized in that: The amine organic compound is selected from one or more of N-methyl-D-glucamine, diethylamine, triethylamine, N-methylacetamide and nitrogen methylformamide.
13. Use of the adsorbent for removing boron and phosphorus impurities in trichlorosilane as claimed in any one of claims 10 to 12, characterized in that: The adsorbent is used for adsorbing boron impurities and phosphorus impurities in trichlorosilane.